The Associations Between Temperament and Self-Oriented, Other-Oriented, and Dual-Harmful Behaviors in Emerging Adults - Serafine Dierickx; Dirk Smits; Glenn Kiekens; Laurence Claes (Psychologica Belgica)
Self- and other-oriented harmful behaviors are common among emerging adults. Individuals who engage in both forms of behavior, termed dual-harm, experience more adverse outcomes in comparison to individuals who engage in either. This study examines temperamental traits, defined as reactive and regulative temperament, as transdiagnostic factors underlying engagement in self-oriented, other-oriented, and dual-harmful behaviors. These harmful behaviors are operationalized as non-suicidal self-injury (NSSI), direct aggression, and a combination of both, respectively. Participants are 669 emerging adults (69.36% women; Mage = 21.48; SD = 2.20). The study focusses on how temperament can differentiate four different groups (i.e., a no-harm, NSSI-only, aggression-only, and a dual-harm group) in a pairwise manner. Results highlight a hyper-reactive Behavioral inhibitions system (BIS) and a hypo-reactive Behavioral activation system (BAS)-Impulsivity in individuals who engage in NSSI-only, compared to no-harm and aggression-only. Conversely, we found a hypo-reactive BIS and a hyper-reactive BAS-Impulsivity in those who report aggressive behaviors, compared to no-harm and NSSI-only. Finally, a hypo-reactive Effortful control (EC) is found in the dual-harm group, when compared to those engaging only in NSSI, and hyper-reactive BIS and BAS-Impulsivity are found in the dual-harm group, when compared to those engaging only in aggressive behaviors, or those engaging in neither behaviors. This study highlights the role of temperamental traits in differentiating patterns of self-oriented, other-oriented, and dual-harmful behaviors, which should be integrated in future research and clinical interventions.